What You Post is What You Get: The Mediator Role of Reached Individuals in the Causal Relationship among Posted Content Types and Follower Counts on Facebook - Flora Poecze (Naše gospodarstvo/Our economy, 2019)
This paper discusses the causal relationships among posted content types, the number of reached individuals and follower counts of a Facebook brand page by investigating the communication forms of a Hungarian Twitch.tv live streamer. The Kolmogorov-Smirnov test for the analyses’ distributional properties is followed by the Kruskal-Wallis H test, which determines significant differences in content types in terms of their total reach, reaction, comment and share counts. The Kendall’s tau-b tests are performed for the examination of interrelationships among the retrieved Facebook metrics. Furthermore, mediation analysis is conducted, wherein the antecedent role is taken by post type, the follower count appears as a consequent variable and the total reach count takes the mediator role in the proposed model. The results of the analysis conclude that the analysed Facebook metrics display statistically significant, strong and positive correlations with one another; additionally, post type has a strong, significant and direct influence on reached individuals and although they do not show a significant, direct influence on follower count, they display a significant, total effect on it. The paper thereby contributes to the existing online brand personality and gaming research, offering value to the research domain of online marketing and communication as well.